(3eLehYI CTYGQ hCRLGd hehGdjGs ((3Ydj Hf MLGRj Hf MjOQ GdSHcj GdTGaYj GdCRgQj s)
(3ChdgG (B:s
(3gPg bUjOI dUaj GdOjf YHOGdYRjR Hf SQGjG GdMdj, hbO SCdg UOjb dg Cf jLeY dg dZI GdZQHGA s
(3BNQgG (B:s
(3ef bUjOI ddTjN YHOGdhgGH Hf jhSa aj eOM GdfHj Udi Gddg Ydjg hSde(B: (3bd dh jGOMGM CQRGfc SMGM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3HgG fXGe GdJYbjHIs
(3hocJHJ Hjf SWhQ GdbUjOI GdChdi eYGfj CdaGXgGs
(3dUaj GdOjf GdMdjs
(3hGdQedjs
(3hGHf fHGJIs
(3hGHf GdMOGOs
Keywords: (3GdCOHs